Legal Status of Credit Bank Guarantee in Indonesia’s Legal Guarantee - Erma Defiana Putriyanti (Faculty of Law, Sriwijaya University, Indonesia, 2017)
The aim of this research is to analyze about the legal status of the letter hiring as collateral for bank loans in the Indonesian security law. The method of this research is a normative juridical. The results of this research indicate that the decree hiring is not included in the objects that can be bound by pledge, fiduciary, and mortgage then hiring decree hiring is not included in the personal guarantee and corporate guarantee. Although the hiring decree is issued by a legitimate institution, the institution is not bound by an agreement between the debtor debts with the bank but when the decree was used as security for the bank. Hiring letter is not also included in the general collateral. Decree hiring is not an object and does not qualify as material that can be used as general collateral. The conclusion of this research is that the position of the decree hiring as collateral for bank loans is a new form of guarantee which is not included in the general guarantees and the specific ones. This shows that the system of legal guarantees in Indonesia is not pure anymore embrace a closed system, but has started shifting into an open system.